A New and Modular Back-to-Back Connected T-Type Inverter for Minimum Number of Power Devices, TSV, and Cost Factor. Issue 2 (4th March 2022) - Mahato, Bidyut; Majumdar, Saikat; Paul, Samrat; Pal, Pradipta Kumar; Jana, Kartick Chandra
Abstract : In this paper, the generalized and new cascaded modular multilevel inverter topology is presented that is designed with reduced power electronic components. Each module comprises ten power switches (2 bi-directional and 8 unidirectional) and five DC sources. Lower voltage rating switches are employed for this topology due to its remarkable advantage of generating both positive and negative voltage levels without using any H-bridge at the output. Various DC voltage magnitude or MLI algorithm of the proposed topology can be selected to obtain different voltage levels. The most optimal inverter algorithm is selected and further design a generalized cascaded structure for high voltage applications that requires lesser components and has better performance. The performance of the proposed optimal algorithm is determined and are compared with the various other state-of-art MLI topologies. The specimen 27-level inverter of the proposed configuration is modulated using the sinusoidal-PWM (SPWM) technique and is implemented in the laboratory prototype of the experimental setup using a d-SPACE 1103 controller. The performance parameters of the proposed topology stand better than other existing and compared MLI topologies in terms of the variety of DC sources, number of DC sources, number of voltage levels, and number of driver circuits. Regarding the economic reliability of the proposed inverter, total standing voltage (TSV), cost factor per level (CFL) have also been calculated. The experimental results of the 27-level output voltage at different load verify its performance.